Pelleted diets for lactating sows - Baudon, E.C.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 76 sows (parities one to four) were used to determine the effects of pelleted diets on sow and litter performance. In the 21-d lactation experiment, the sows were given a corn-soybean meal-based diet in meal (corn ground to a particle size of 500 to 600 μm) or a pelleted (3/16 inch pellet diameter) form. Diet form did not affect ADFI or lactation BW loss (P=0.15 or greater). Also, pigs weaned per litter, piglet survivability, litter weight gain, and days to estrus were not affected by treatment (P=0.15 or greater). However, sows fed pelleted feed lost less backfat (0.05 inches, P<0.02). Also, when the diet was pelleted, the sows had 6, 9, and 9% greater digestibilities of DM, N and GE and excretion of DM and N were decreased by 90 g/d and 2 g/d, respectively (P<0.001). In conclusion, use of pelleted feed in mixed-parity sows did not affect litter performance, but increased digestibility of nutrients and reduced nutrient excretion in sows.
Keywords: Sow; Pellets; Lactation; Digestibility; Swine